PENGEMBANGAN PERANGKAT PEMBELAJARAN IPA BERBASIS MODEL PEMBELAJARAN PREDICT OBSERVE EXPLAIN UNTUK MENINGKATKAN PEMAHAMAN KONSEP SISWA PADA MATERI TATA SURYA - Ayu Nofsi Putri; Yennita Yennita; Mitri Irianti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The learning device developed are science learning device based on the POE model to improve the conceptual understanding of seventh grade junior high school students on the material of the solar system, consisting of a Learning Implementation Plan (RPP), Student Worksheets (LKPD), and Concept Understanding Test Instruments. The purpose of this study was to produce a valid POE-based science learning device and be used to improve students' conceptual understanding of the solar system material. This research is expected to be a reference for making innovative learning device and can be used as a foundation in the teaching and learning process so that learning objectives can be achieved. This type of research is a Research and Development (R&D) using the 4D model. This research is only limited to the development stage. The research instrument used was the RPP validation assessment sheet, LKPD, and the Concept Understanding Test Instrument used by the validator to assess learning device. Data analysis in this study used descriptive analysis, by calculating the validity score of each indicator of the learning device. The results of the study concluded that the science learning device based on the POE model was declared valid and suitable for teaching in seventh grade junior high school students to improve students' understanding of the concept of the solar system material.Key Words: Science Learning Device, POE Model, Understanding of the Concept, Solar System